2018
DOI: 10.1136/bmjopen-2017-018734
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in oculomotor function in young adults with mild traumatic brain injury in Sweden: an exploratory prospective observational study

Abstract: ObjectivesTo assess (1) whether visual disturbances can be demonstrated with objective measures more often in patients with mild traumatic brain injury (mTBI) than in orthopaedic controls and non-injured controls, (2) whether such objectively demonstrated disturbances change over time and (3) whether self-reported visual symptoms after mTBI correlate with objectively measurable changes in visuomotor performance.DesignA prospective, controlled, observational study, with assessments planned 7–10 and 75–100 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…McDevitt et al 36 demonstrated that the mean NPC distance was larger in the concussed group compared with the control group, but it was not statistically significant. Matuseviciene et al 35 demonstrated a significant improvement in the mTBI group between baseline and followup, but no statistically significant difference between or within the control groups. Two studies 34,35 did not report means for NPC but presented statistical results for the comparison of measures.…”
Section: Evidence Synthesismentioning
confidence: 94%
See 4 more Smart Citations
“…McDevitt et al 36 demonstrated that the mean NPC distance was larger in the concussed group compared with the control group, but it was not statistically significant. Matuseviciene et al 35 demonstrated a significant improvement in the mTBI group between baseline and followup, but no statistically significant difference between or within the control groups. Two studies 34,35 did not report means for NPC but presented statistical results for the comparison of measures.…”
Section: Evidence Synthesismentioning
confidence: 94%
“…Matuseviciene et al 35 demonstrated a significant improvement in the mTBI group between baseline and followup, but no statistically significant difference between or within the control groups. Two studies 34,35 did not report means for NPC but presented statistical results for the comparison of measures. All of the means presented for NPC during initial assessments following injury were abnormal (>5 cm).…”
Section: Evidence Synthesismentioning
confidence: 94%
See 3 more Smart Citations